PENGEMBANGAN MEDIA SOFCAR (SOLAR SYSTEM FLASHCARD AUGMENTED REALITY) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM TATA SURYA KELAS VI SEKOLAH DASAR - Tiana; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science learning at UPT SDN Tambakboyo 1 has not been optimally implemented. Students' science learning outcomes are still below the Kriteria Ketercapaian Tujuan Pembelajaran (KKTP). This study aims to develop augmented reality-based flashcard learning media called SOFCAR (Solar System Flashcard Augmented Reality) to improve student learning outcomes. Research data were collected from sixth-grade students at UPT SDN Tambakboyo 1, Tambakboyo District, Tuban Regency, East Java. The research method used was Research and Development (R&D), employing the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The results of the learning media development were found to be highly valid and capable of improving student learning outcomes. Validity testing showed a percentage of 85% from subject matter experts, 82.85% from media experts, and 85% from language experts. Practicality testing showed a percentage of 94% from teacher response questionnaires and 96% from student response questionnaires, indicating that the achieved percentages fall within the criteria for highly practical. The effectiveness test of the product through N-Gain analysis showed that 100% of the students achieved mastery on the post-test sheets from 27 students. Student learning outcomes showed significant improvement compared to the pre-test, where only 12 students achieved mastery of the KKTP. Therefore, the use of SOFCAR or augmented reality-based flashcards is effective for use in the learning process.